Enzymatic saccharification of hemicellulose extracted from palm oil mill wastes - Poonsuk Prasertsan; Susumu Oi (Songklanakarin Journal of Science and Technology (SJST), 2001)
Various parameters affecting the extraction of hemicellulose from palm cake by alkali method and sterilizer condensate by solvent method were investigated. For extraction of hemicellulose from palm cake, the optimal ratio of palm cake to sodium hydroxide (NaOH) (1.5% conc.) was 1:10. However, potassium hydroxide (KOH) was a better source of alkali than NaOH and the optimum ratio of palm cake to 12% KOH was 1:50 (w/v). Temperature over 100ºC (100 and 121ºC) extracted significantly higher hemicellulose than at 80ºC after 20 min treatment. The addition of ethanol to the extracted solution in the ratio of 1:1 (v/v) gave the highest hemicellulose yield of 8.67 g/100 g palm cake. For extraction of hemicellulose from sterilizer condensate, the optimum ratio of ethanol to the condensate was 2:1 (v/v), which gave a hemicellulose yield of 6.42 g/100 ml. The enzymatic saccharification of the hemicelllulose extracted from palm cake (HEPC) and from sterilizer condensate (HESC) was 3-10 times lower than that of xylan. The enzyme from Aspergillus niger ATCC 6275 and Meicellase gave higher saccharification rates than that of Sumyzyme. The contents of reducing sugars in xylan, HEPC and HESC were 96.4, 36.2 and 20.6%, respectively and 75.3, 67.9 and 97.6% of these values could be hydrolysed by the enzymes. Hence, palm cake was a better source of substrate for extraction of hemicellulose while hemicellulose extracted from sterilizer condensate gave higher percentage of enzymatic saccharification.